Adaptive output feedback control of uncertain nonlinear systems with hysteresis nonlinearity - Zhou, Jing (2013)
In this note, we consider a class of uncertain dynamic nonlinear systems preceded by Bouc-Wen type of hysteresis nonlinearity. A new perfect inverse function of the hysteresis is constructed and used to cancel the hysteresis effects in controller design with backstepping technique. For the design and implementation of the controller, no knowledge is assumed on system parameters. It is shown that the proposed controller not only guarantees asymptotic stability, but also transient performance.